The Effect of Folic Acid Supplementation on the Liver Function in Chronic Schizophrenia Patients - Fitrikasari, Alifiati; Asady, Julianata; Jusup, Innawati; Asikin, Hang Gunawan (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2023)
Oxidative stress caused by free radicals and long-term antipsychotic use in chronic schizophrenic patients may result in liver cell damage and impaired liver function. Folic acid is an exogenous antioxidant that can boost the antioxidant defense mechanism (Glutathione Reductase), lowering free radicals and improving liver function. Determine the correlation between adjuvant folic acid and liver function in chronic schizophrenic patients. This was a placebo-controlled, double-blinded randomized control trial. The study sample included 36 patients in the control group and 36 patients in the treatment group. Subjects were patients who had suffered from schizophrenia for at least 2 years and received antipsychotics. Research subjects in the treatment group received folic acid supplementation. The intervention was conducted for 21 days during hospitalization. The level of AST (U/L) and ALT (U/L) was measured before and after supplementation. Following folic acid supplementation, AST levels were significantly improved (26.950 U/L compared to prior to treatment 33.09 U/L, p= <0.001). ALT levels after treatment were increased but there was no significant difference observed (p= 0.835). Folic acid supplementation improves AST levels significantly.